THE RELATIONSHIP OF RESILIENCE WITH BASIC MATHEMATICS LEARNING OUTCOMES OF PGMI STUDENTS - Siregar, Novi Ismaliza; Mustadi, Ali; Sulistyowati, Endang (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2024)
Students still need help learning mathematics and completing assignments. Various things can cause this. One of them is the pressure of facing basic mathematics learning. This research aims to determine the relationship between mathematical resilience and learning outcomes in basic mathematics courses for PGMI UIN Sunan Kalijaga Yogyakarta students. The sample for this research consisted of 33 PGMI UIN Sunan Kalijaga students. The research method used is the correlation research method. Data collection techniques use research instruments in the form of test and non-test instruments. The test instrument used in this research is questions to measure mathematics learning outcomes, while the non-test instrument uses a questionnaire to measure mathematical resilience. The data analysis technique uses descriptive data analysis, prerequisite tests (normality and homogeneity tests), and hypothesis testing using the product moment correlation formula. The results of this research show that there is a significant relationship between resilience and mathematics learning outcomes for class C PGMI UIN Sunan Kalijaga students.